1995
DOI: 10.1029/95wr01584
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Groundwater Dating, Chemical, and Isotopic Analyses to Resolve the History and Fate of Nitrate Contamination in Two Agricultural Watersheds, Atlantic Coastal Plain, Maryland

Abstract: The history and fate of groundwater nitrate (NO•-) contamination were compared in 2 small adjacent agricultural watersheds in the Atlantic coastal plain by combined use of chronologic (CC12F2, 3H), chemical (dissolved solids, gases), and isotopic (•15N, •13C, •34S) analyses of recharging groundwaters, discharging groundwaters, and surface waters. The results demonstrate the interactive effects of changing agricultural practices, groundwater residence times, and local geologic features on the transfer of NO•thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
581
3
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 632 publications
(631 citation statements)
references
References 47 publications
39
581
3
3
Order By: Relevance
“…Relations between groundwater nitrate concentration and N fertilizer or agricultural land use are well-documented (2,13,21,37,38). Relations among percent population density, percent well-drained soils, and depth to the seasonally high water table are consistent with the previous model (20).…”
Section: Recalibration Of Multivariate Logistic Regression Modelsupporting
confidence: 66%
“…Relations between groundwater nitrate concentration and N fertilizer or agricultural land use are well-documented (2,13,21,37,38). Relations among percent population density, percent well-drained soils, and depth to the seasonally high water table are consistent with the previous model (20).…”
Section: Recalibration Of Multivariate Logistic Regression Modelsupporting
confidence: 66%
“…For this reason, if the presence of excess air is not considered in the calculation of an SF6 model age, then the apparent age will be too young. The error in the age due to the presence of excess air is less than 1 year for pre-1990 waters dated with CFCs [Busenberg and Plummer, 1992] but can be significant for younger waters. Excess air can introduce a significant error when dating groundwater with SF6 because the Henry's law constant of SF6 is approximately 55 and 13 times smaller than that of CFC-11 and CFC-12, respectively.…”
Section: Evaluation Of the Recharge Temperaturementioning
confidence: 99%
“…Similar results were inferred from a study of nitrate in regional groundwater and nitrate levels in streamflow for the WDU hydrogeomorphic region (Phillips and others 1993). In related work, Bohlke and Denver (1995) concluded that a riparian forest wetland next to a stream in the WDU had little effect on nitrate movement to the stream. Hydrologic data and groundwater flow modeling showed that groundwater discharges upward directly to the streambed from the aquifer system, effectively bypassing the riparian zone (Reilly and others 1994).…”
Section: Nitrate Transport In Shallow Groundwatermentioning
confidence: 99%
“…The general conclusion of all these studies was that denitrification occurred in most riparian forest soils, especially in the root zone, or that conditions were favorable for denitrification. Recent work by Bohlke and Denver (1995) indicated that denitrification can also occur in aquifer sediments below the influence of the riparian root zone where proper geochemical environments exist. Isotopic analy- sis of groundwater and streamflow at this site indicated that denitrification was not significantly reducing nitrate concentrations (Bohlke and Denver 1995).…”
Section: Vegetation Uptake and Denitrificationmentioning
confidence: 99%
See 1 more Smart Citation